2013
DOI: 10.1002/dneu.22141
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the axonal trafficking of nuclear‐encoded mitochondrial mRNA alters neuronal mitochondrial activity and mouse behavior

Abstract: Local translation of nuclear-encoded mitochondrial mRNAs is essential for mitochondrial activity, yet there is little insight into the role that axonal trafficking of these transcripts play in neuronal function and behavior. Previously, we identified a 38 nucleotide stem-loop structure (zipcode) in the 3′ untranslated region of the Cytochrome C oxidase IV (COXIV) mRNA that directs the transport of a reporter mRNA to the axon of superior cervical ganglion neurons (SCG). Over-expression of a chimeric reporter mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Axons depleted of LB2 mRNA degenerate even after they have reached their targets, suggesting that they rely on intra-axonal synthesis of laminB2 not only during development, but also after maturation. Finally, interference with axonal transport of the nuclear-encoded mitochondrial mRNA of cytochrome C oxidase IV was found to impact on neuronal mitochondrial function leading to altered mouse behavior [27]. Together, these findings strongly suggest that the ability for protein synthesis persists in postdevelopmental axons in vivo.…”
Section: Intra-axonal Protein Synthesismentioning
confidence: 87%
See 1 more Smart Citation
“…Axons depleted of LB2 mRNA degenerate even after they have reached their targets, suggesting that they rely on intra-axonal synthesis of laminB2 not only during development, but also after maturation. Finally, interference with axonal transport of the nuclear-encoded mitochondrial mRNA of cytochrome C oxidase IV was found to impact on neuronal mitochondrial function leading to altered mouse behavior [27]. Together, these findings strongly suggest that the ability for protein synthesis persists in postdevelopmental axons in vivo.…”
Section: Intra-axonal Protein Synthesismentioning
confidence: 87%
“…Thus, in theory, it might be sufficient to overexpress the entire the 3'UTR of an mRNA of interest in order to interfere with its localization or translation in axons. Indeed, such an approach has been followed successfully in genetically modified mice [27].…”
Section: Toolsmentioning
confidence: 99%
“…Several prior studies have demonstrated the importance of local translation for axon maintenance (Yoon et al, 2012), mitochondrial function (Kar et al, 2014) and survival (Cox et al, 2008), and suppression of local translation of lb2 mRNA causes neurodegeneration in vivo (Yoon et al, 2012). Here we report another dimension of local protein synthesis: in response to a physiologically relevant neurodegenerative stimulus axonal protein synthesis plays an active role in the transmission of neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…After the developmental period, the composition of the axonally localized transcriptome changes (Gumy et al, 2011), overall levels of mRNAs and ribosomes are lower (Kleiman et al, 1994), and mature axons have long been thought to be incapable of protein synthesis. However, recent evidence shows that protein synthesis persists in post-developmental CNS axons in vivo (Dubacq et al, 2009; Kar et al, 2014; Willis et al, 2011; Yoon et al, 2012). Additionally, upon injury of mature axons, a specific set of mRNAs and translation machinery are rapidly recruited into axons, and proteins are locally synthesized within mature axons (Rishal and Fainzilber, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lamin b2 mRNA is localized to retinal axons in Xenopues laevis tadpoles and its depletion affects axon maintenance after axonal development 21 . Interference with the axonal transport of the mRNA encoding for cytochrome C oxidase IV alters mouse behavior 24 . Finally, Atf4 mRNA is found in adult axons of mice and human brains in the context of Aβ 1-42 -induced neurodegeneration 18 .…”
Section: Introductionmentioning
confidence: 99%